The Role of Primary Tumor Resection in Patients With Pancreatic Neuroendocrine Tumors With Liver Metastases - Mou, Yu; Wang, Zi-Yao; Tan, Chun-Lu; Chen, Yong-Hua; Liu, Xu-Bao; Ke, Neng-Wen (Frontiers in Oncology, 2022)
Background: Liver metastases (LM) are common in advanced pancreatic neuroendocrine tumors (PNETs) patients. Now the benefit of primary tumor resection (PTR) in the setting of PNETs patients with liver metastases is still controversial in several guidelines. Methods: Data were extracted from the Surveillance, Epidemiology and End Results (SEER) database to evaluate this issue. The main interesting index in our study was overall survival time. Results: Information of 536 PNETs patients with liver metastases from SEER database was identified. 214 patients received primary tumor resection and more than half of them (132 patients) had synchronous LM resection. Significantly survival benefit were gained from PTR when compared with non-PTR patients, both in OS (72.93±2.7 months vs. 36.80±2.22 months) and 3- or 5-year survival rate (75.1% vs. 28.9% and 67.9% vs. 22.3% respectively). No difference was found between PTR alone and PTR with synchronous LM resection. From univariate and multivariate analysis, younger age (< 65 years) and well- or moderately tumor differentiation may be more priority when considering primary tumor resection. However, we found that all grade of tumor differentiation could gain a better overall survival time after primary tumor resection. Conclusion: Our study suggested that the primary tumor resection in pancreatic neuroendocrine patients with liver metastases could result in a longer survival time. Primary tumor resection with synchronous liver metastases resection did not relate a better survival benefit. This treatment strategy may routinely be taken into consideration in these patients.